Application of real-time polymerase chain reaction using species specific primer targeting on mitochondrial cytochrome-b gene for analysis of pork in meatball products - Orbayinah, Salmah; Widada, Hari; Hermawan, Adam; Sudjadi, Sismindari; Rohman, Abdul (Journal of Advanced Veterinary and Animal Research, 2019)
Objective: This study aimed to design specific primers derived from mitochondrial cytb of Sus Scrofa (1F1R primer) used in the pork meatball analysis using real time polymerase chain reaction (RT-PCR) method. Materials and Methods: Such designed primers were validated and these included specificity of primer, linearity, and sensitivity of the method as well as the repeatability test. The primers were specifically affirmed in the fresh tissue of chickens, cows, pigs, and goats. The linearity and sensitivity of the method was conducted by measuring the amplification curve from a series of dilution (0, 1, 1, 10, 100, 1,000, and 10,000 pg/μl of DNA) extracted from 100% pork meatball formulation. The repeatability test was conducted by determining the cycle threshold (Ct) values of RT-PCR amplification from 100% pork meatball formulation as many as six times. Results: Primer of 1F1R (forward: 5′-ACG CGA TAT AAG CAG GTA AA-3′; reverse: 5′-CTG CTT TCG TAG CAC GTA TT-3′) was specific in analyzing the presence of pork in meatball formulation at 47.1°C, which was optimum annealing temperature. The DNA identification was able to use the primers by RT-PCR with 1 pg as the limit of detection, efficiency value was 242.58%, and the coefficient of determination value (R2) was 0.956. The coefficient of variance was 4.13%. The developed method was also fruitfully applied to analyze commercial meatballs. Conclusion: RT-PCR method using specific primers targeting on mitochondrial gene (1F1R primer) could be used as the standard method for identification of pork in food samples intended for halal authentication studies. J. Adv. Vet. Anim. Res., 6(2): 260-265, June 2019